2005
DOI: 10.1088/0953-8984/17/48/l02
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and Jahn–Teller instabilities in a single vacancy in Ge

Abstract: Density functional modelling studies of the single vacancy in large Ge clusters are presented. We take a careful look at the origin of Jahn–Teller instabilities as a function of the vacancy net charge, resulting in a variety of structural relaxations. By comparing electron affinities of the vacancy with those from defects with well established gap states, we were able to estimate three acceptor states for the vacancy at E(−/0) = Ev+0.2 eV, E(=/−) = Ec−0.5 eV and  eV. As opposed to the Si vacancy, the defect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 27 publications
(47 reference statements)
3
25
0
Order By: Relevance
“…Similar modeling of the vacancy in germanium found it to possess single and double acceptor levels close to E v 0:2 eV [5], in agreement with experiment [20]. Its migration barrier is charge dependent, varying between 0.3 eV for V 2ÿ and 0.7 eV for V 0 [23].…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Similar modeling of the vacancy in germanium found it to possess single and double acceptor levels close to E v 0:2 eV [5], in agreement with experiment [20]. Its migration barrier is charge dependent, varying between 0.3 eV for V 2ÿ and 0.7 eV for V 0 [23].…”
supporting
confidence: 71%
“…It seems paradoxical that defects containing broken bonds should be electrically inert. In contrast with p-Ge, irradiation of n-Ge leads to the formation of Frenkel pairs stable up to 65 K. These are double acceptors [4] and readily understood in terms of charged vacancies [5] with a nearby neutral interstitial. Thus it seems that at 4 K, electron irradiation introduces interstitials in a neutral charge state both in n-Ge and p-Ge.…”
mentioning
confidence: 99%
“…Once we excluded that at higher temperatures As does not have an effect on doping the layer and comes from the growth chamber from previous growths, we can make the hypothesis on the origin of the unwanted p-type doping. We can suppose that it may come: (a) from the iBuGe source, which cannot be as pure as from the datasheet, (b) from other elements that out-diffuse from the reactor environment (Ga, In) due to previous growth and (c) from Ge vacancies incorporated in the crystal lattice, that have acceptorlike behaviour [9]. SIMS measurements are planned in order to have insights on the origin of the p-type behaviour and to discern between these cases.…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical calculations 23,24 also strongly indicated the existence of the triple negatively charged vacancy in Ge, which bound to P þ as PV 2À . What is more, the deep level transient spectroscopy (DLTS) studies on irradiation induced defects in n-type Ge suggested that a double acceptor level was in the upper half of the Ge bandgap.…”
mentioning
confidence: 91%